Nanoemulsion and topical cream for delivery of tocotrienol-rich fraction, ascorbyl tetraisopalmitate, and carotenes: formulation and in vitro release - Gan, Yee-Lin; Chin, Ping Tan; Cheah, Yoke Kqueen; Ariffin, Hidayah; Wasoh, Helmi; Oi, Ming Lai (Universiti Putra Malaysia, 2025)
Objectives of this study were to encapsulate tocotrienol-rich fraction (TRF), ascorbyl tetraisopalmitate (AT) and carotenes into nanoemulsion, incorporate the formulated nanoemulsion into moisturizer cream, and characterize the formulated nanoemulsion and cream. A stepwise factorial design methodology was used to screen the nanoemulsion’s ingredients and preparation parameters. With mean droplet size, polydispersity index (PDI), creaming index (CI) and irritational potential as evaluation criteria, the ideal nanoemulsion formulation comprised deionized water, red palm oil (RPO) and Kolliphor® EL in a ratio of 20.00:6.25:73.75, fabricated using a high-shear mixer at 7000 rpm and 45°C for 10 min followed by a high-pressure homogenizer at 750 bars for five cycles. The nanoemulsion’s mean droplet size and PDI were 121.5 ± 1.8 nm and 0.178 ± 0.010, respectively. The cream formulation was then screened using a factorial experiment that considered lipid and emulsifier concentrations. The optimal cream formulation contained deionized water, formulated nanoemulsion, petrolatum, mineral oil, glycerol, emulsifying wax and carbomer 940 in a ratio of 66.8:10.0:7.5:7.5:5.0:3.0:0.2, showing the preferred shear-thinning behavior, excellent physical stability and high conclusiveness. The formulated cream exhibited Korsmeyer-Peppas and Weibull release kinetic mechanisms during the in vitro release. This study showed that the developed formulations were suitable for the topical delivery system for TRF, AT and carotenes.